Barreiras não-tarifárias e acordos regionais de livre-comércio: um estudo das exportações de manga para a América do Norte - Xavier, Lucas Moura (2021)
Based on a discussion about the world market for mangoes and the insertion of Brazil in this market due to the vigorous dynamism of the states of Bahia and Pernambuco through the Petrolina-Juazeiro Irrigated Fruit Farming Pole, this paper provides an overview of the effects of barriers non-tariff and NAFTA on Brazilian mango exports to North America. The choice of North America as the object of this study was due to the presence of the main world mango importer in this subcontinent, the United States of America, and the dominance of Mexico over this market, which raises suspicions of protectionism through barriers, especially the of a non-tariff nature, such as technical, sanitary and phytosanitary barriers. To achieve the objective of this work, a vast bibliographical and documental review was used, as well as two main methodological approaches: the price-wedge method, which allows the calculation of an equivalent tariff for non-tariff barriers; and the gravitational model, which in addition to its classic variables, GDP and distance, included a dummy for NAFTA, in order to verify the effects of this block on Brazilian mango exports. The results of the work indicated that there is no evidence that the non-tariff barriers applied by North America are being used in an arbitrary way and without a plausible justification, just selecting the fruits of adequate quality; while for NAFTA it was observed that it has a positive effect on Brazilian exports.